Medical Imaging 2019: Digital Pathology 2019
DOI: 10.1117/12.2512892
|View full text |Cite
|
Sign up to set email alerts
|

Joint region and nucleus segmentation for characterization of tumor infiltrating lymphocytes in breast cancer

Abstract: Histologic assessment of stromal tumor infiltrating lymphocytes (sTIL) as a surrogate of the host immune response has been shown to be prognostic and potentially chemo-predictive in triplenegative and HER2-positive breast cancers. The current practice of manual assessment is prone to intra-and inter-observer variability. Furthermore, the interplay of sTILs, tumor cells, other microenvironment mediators, their spatial relationships, quantity, and other image-based features have yet to be determined exhaustively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 4 publications
0
34
0
Order By: Relevance
“…For instance, Amgad et al 23 has developed an effective deep-learning–based method for joint region-level and nucleus-level segmentation of TILs, even though their work was limited by the lack of validation on large-scale image datasets and additional analysis between spatial TIL features and biologic data. Saltz et al 24 have presented global mappings, as well as the spatial organization and molecular correlation of TILs for over 5,000 H&E diagnostic WSIs from The Cancer Genome Atlas (TCGA) dataset, which represented a benchmark for TIL analysis.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Amgad et al 23 has developed an effective deep-learning–based method for joint region-level and nucleus-level segmentation of TILs, even though their work was limited by the lack of validation on large-scale image datasets and additional analysis between spatial TIL features and biologic data. Saltz et al 24 have presented global mappings, as well as the spatial organization and molecular correlation of TILs for over 5,000 H&E diagnostic WSIs from The Cancer Genome Atlas (TCGA) dataset, which represented a benchmark for TIL analysis.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that for this particular dataset, the VGG-16 FCN-8 architecture shows more favorable model convergence and fitting properties than the deeper and more complex DenseNet architecture [29]. Using this particular architecture and number of layers enabled us to leverage the publicly available pre-trained weights, hence improving accuracy [28,29]. The model is trained to classify pixels into one of five classes: tumor (including DCIS), stroma, tumor-infiltrating lymphocytes (including plasma cells and mixed inflammatory infiltrates), necrosis or debris, and others.…”
Section: The Breast Cancer Histological Image Analysis Fully-convolutmentioning
confidence: 90%
“…To extract tumor features we used our established standard 16-layer VGG fully-convolutional neural network (VGG16-FCN8) constructed using ImageNet [ 27 ] pre-trained weights as described previously [ 28 ]. We have previously shown that for this particular dataset, the VGG-16 FCN-8 architecture shows more favorable model convergence and fitting properties than the deeper and more complex DenseNet architecture [ 29 ]. Using this particular architecture and number of layers enabled us to leverage the publicly available pre-trained weights, hence improving accuracy [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of computational TILs have employed patch- or object detection-based approaches [ 26 , 27 , 28 , 29 ] with manual region outlining as part of the pipeline [ 30 ]. Some of these also used multiplexed immunofluorescence (mIF) [ 31 ] or immunohistochemistry (IHC) [ 32 , 33 ] to classify cells as lymphocytes.…”
Section: Introductionmentioning
confidence: 99%